Southern African agriculture and climate change: A comprehensive analysis - Botswana - Zhou, Peter P.; Simbini, Tichakunda; Ramokgotlwane, Gorata; Hachigonta, Sepo; Sibanda, Lindiwe M.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Botswana that will appear in the peer-reviewed IFPRI monograph, Southern African Agriculture and Climate Change: A Comprehensive Analysis.